THE LEADER'S ROLE IN STAFF MOBILIZATION TO REALIZE THE GOALS OF EDUCATIONAL INSTITUTIONS - Achmad Bagus Sugiarto (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
The problem of mobilization is closely related to people and is one of the most complex and difficult problems of all management functions, because no matter how modern the equipment, without the support of people as actors it means nothing. Mobilizing people is difficult because human workers are living beings with different self-esteem, feelings and goals. This mobilizing function can be compared to a car key, the car will only move if the state lock has worked.The role of the leader as key holder is very important to note and pay attention to. Especially when that leader is leading an educational institution which has the peculiarity that the leader is a human being, the led is a human being, and the goal is to print humans. For this reason, the purpose of this brief journal is to explain the urgency of this matter and to give a brief analysis of it.